Embolisation of hypervascular bone tumours: A pictorial essay with literature review. Issue 2 (12th September 2012) - Lau, Vince; Sun, Michael; Chu, Ferdinand
Summary Bone tumours, either primary or secondary, can present in various debilitating manners, including pain and pathological fracture. The situation is particularly problematic when the tumours are hypervascular, and located in regions where a high risk of neurological compromise is anticipated during operation, such as in the spine or sacrum. In such situations, bone tumour embolisation is a useful and effective adjunctive treatment for reducing intra‐operative blood loss. This is particularly relevant in primary bone tumours such as giant cell tumours and metastatic renal cell and thyroid tumours. With a proper pre‐embolisation angiogram and knowledge of anatomy, careful selective cannulation of the arterial supplies and experience in using embolic agents, the risks of non‐target embolisation can be kept to minimum and the best result achieved.